2018
DOI: 10.1002/adfm.201803804
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment‐Responsive Mesoporous MnO2‐Coated Upconversion Nanoplatform for Self‐Enhanced Tumor Theranostics

Abstract: The insufficient blood flow and oxygen supply in solid tumor cause hypoxia, which leads to low sensitivity of tumorous cells and thus causing poor treatment outcome. Here, mesoporous manganese dioxide (mMnO 2 ) with ultrasensitive biodegradability in a tumor microenvironment (TME) is grown on upconversion photodynamic nanoparticles for not only TME-enhanced bioimaging and drug release, but also for relieving tumor hypoxia, thereby markedly improving photodynamic therapy (PDT). In this nanoplatform, mesoporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(179 citation statements)
references
References 77 publications
(34 reference statements)
1
170
0
3
Order By: Relevance
“…While the PMLR sample treated with H 2 O 2 at an acidic environment exhibited enhanced T 1 signal, and the initial longitudinal relaxivity r 1 increased to 7.83 m m −1 s −1 , which was close to the recent activatable MRI contrast agents and commercial contrast agents reported in the previous literatures . The enhancement of T 1 signal resulted from the release of Mn 2+ , the magnetic moments and paramagnetic center of which led to the large longitudinal relaxation rate for MRI . All these results demonstrated that PMLR nanosystem might exhibit tumor‐sensitive MRI effect, since tumor tissues overexpress H 2 O 2 and the lysosomes of tumor cells are acidic (pH 4.0–5.0) …”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…While the PMLR sample treated with H 2 O 2 at an acidic environment exhibited enhanced T 1 signal, and the initial longitudinal relaxivity r 1 increased to 7.83 m m −1 s −1 , which was close to the recent activatable MRI contrast agents and commercial contrast agents reported in the previous literatures . The enhancement of T 1 signal resulted from the release of Mn 2+ , the magnetic moments and paramagnetic center of which led to the large longitudinal relaxation rate for MRI . All these results demonstrated that PMLR nanosystem might exhibit tumor‐sensitive MRI effect, since tumor tissues overexpress H 2 O 2 and the lysosomes of tumor cells are acidic (pH 4.0–5.0) …”
Section: Methodsmentioning
confidence: 92%
“…[36,37] The enhancement of T 1 signal resulted from the release of Mn 2+ , the magnetic moments and paramagnetic center of which led to the large longitudinal relaxation rate for MRI. [35] All these results demo nstrated that PMLR nanosystem might exhibit tumorsensitive MRI effect, since tumor tissues overexpress H 2 O 2 and the lys osomes of tumor cells are acidic (pH 4.0-5.0). [38] As mouse melanoma tumors exhibit the Warburg pheno type (with strong aerobic glycolysis), [13] B16F10 cell line was chosen for the further study.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 95%
“…Interestingly, tumors often over‐express hydrogen peroxide (H 2 O 2 , usually at a generation rate of 5 nmol per 10 5 cells h −1 ), and H 2 O 2 could be a source for O 2 production within tumors . Thus, various kinds of nanoparticle‐based catalysts/enzymes have been constructed to catalyze the decomposition of H 2 O 2 to generate O 2 for ameliorating tumor hypoxia, including MnO 2 , CaO 2 , carbon nitride, carbon dots, biological catalase, and others . These reported nanoplatforms have shown outstanding catalytic activity for in situ endogenous O 2 generation, consequently leading to high therapeutic effect on account of the production of highly cytotoxic 1 O 2 under near‐infrared (NIR) light irradiation .…”
Section: Methodsmentioning
confidence: 99%
“…Of late, PDT is considered to be a promising modality for treating tumors, [67][68][69][70][71][72][73][74][75][76] glaucoma, and so on [77] because of its advantages, including minimal invasiveness and high spatial selectivity. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] More importantly, by employing their unique merits, UCNPs have also shown potential application in inhibiting Aβ aggregation. [79] To address these challenges, rare earth upconversion nanoparticles (UCNPs) have been utilized as energy transducers to indirectly activate PS by using NIR light as excitation source.…”
Section: Pdt For Admentioning
confidence: 99%